Theoretical and methodological framework for measuring the robustness of social institutions in education and training - Ursula Renold; Ladina Rageth; Katherine Caves; Jutta Buergi (ETH Zurich, KOF Swiss Economic Institute, 2019)
Social institutions are relatively stable patterns of behavior or joint action that help overcome fundamental problems and perform a function in society. The robustness of such institutions underlies their effectiveness at solving problems, but such robustness is difficult to assess. Building on different institutionalism approaches, this paper first develops a theoretical framework of social institutions. This framework combines Miller's properties of social institutions - function, structure, culture, and sanction - with a temporal dimension (i.e., level of institutionalization) and a spatial one (i.e., scope of the institution). Our methodological approach then shows how scholars can use the framework to assess the robustness of a given institution. Second, this paper applies that framework to the social institutions in education and training programs. To identify functional equivalents across such programs in all contexts, we elaborate on field-specific theoretical concepts. By applying the methodological approach, scholars can assess the social institutions carrying out those functions. We hypothesize that robust social institutions are robust in all properties and dimensions, and that robust education and training programs are composed of individual robust social institutions.
Keywords: 330; Social institutions; new institutionalism; education and training; vocational education and training programs; functional equivalents